DIETARY THERAPY IN THE TREATMENT OF EOSINOPHILIC ESOPHAGITIS: A COMPREHENSIVE REVIEW OF CLINICAL EVIDENCE - Maria Wieczorek,; Jan Kownacki,; Paweł Drzymała,; Kacper T. Majczak,; Marta Śliwińska,; Magdalena G. Gehrke,; Aleksandra Schmidt,; Julian Uchacz,; Oliwia Z. Śmiechowicz,; Natalia A. Skwarek, (International Journal of Innovative Technologies in Social Science, 2026)
Eosinophilic esophagitis (EoE) is a chronic, immune-mediated inflammatory disorder of the esophagus characterized clinically by symptoms of esophageal dysfunction and by eosinophilic infiltration. EoE has emerged as a major cause of dysphagia and food impaction in both pediatric and adult populations. Accumulating evidence indicates that is primarily driven by antigen exposure, particularly food allergens, leading to a T helper type 2 (Th2)-mediated inflammatory cascade. Dietary therapy has become one of the three major therapeutic pillars of EoE management, alongside proton pump inhibitors and topical corticosteroids. This review synthesizes current evidence regarding dietary interventions in EoE and demonstrates that dietary therapy induces histologic remission in a substantial proportion of patients, with response rates exceeding 90% for elemental diets and approximately 70% for six-food elimination diets. However, dietary treatment carries risks of nutritional deficiencies, psychosocial burden, and the need for repeated endoscopic monitoring.